Extracellular vesicles derived from macrophages: Current applications and prospects in tumors - Lou, Kecheng; Feng, Shangzhi; Luo, Hui; Zou, Junrong; Zhang, Guoxi; Zou, Xiaofeng (Frontiers in Bioengineering and Biotechnology, 2022)
Macrophages (Mφs) are major innate immune cells that exhibit different functions in response to different pathogens or stimuli. They are widely engaged in the pathological processes of various diseases and can contribute to tumorigenesis, progression and metastasis through regulation of the tumor microenvironment and cancer cells, and are also the basis of chemoresistance. In turn, the tumor microenvironment and the metabolism of cancer cells can restrict the differentiation, polarization, mobilization and the ability of Mφs to initiate an effective anti-tumor response. Extracellular vesicles (EVs) are small vesicles released by living cells, which are important mediators of intercellular cell communication and also a potential promising drug carrier. A growing number of studies have shown that Mφs-EVs are not only important mediators in the pathological processes of various diseases such as inflammatory diseases, fibrosis and cancer, but also show important potential in immune regulation, cancer therapy, infectious defense and tissue repair. These natural nanoparticles (NPs) derived from Mφs are believed to be pleiotropic, stable, biocompatible and low immunogenic, offering novel options for cancer treatment. This review provides an update on the pathological and therapeutic roles of Mφs-EVs in cancer, as well as their potential clinical applications and future perspectives.